Clickable C-Glycosyl Scaffold for the Development of a Dual Fluorescent and [18F]fluorinated Cyanine-Containing Probe and Preliminary In Vitro/Vivo Evaluation by Fluorescence Imaging - Julen Ariztia; Kamal Jouad; Valérie Jouan-Hureaux; Julien Pierson; Charlotte Collet; Bertrand Kuhnast; Katalin Selmeczi; Cédric Boura; Sandrine Lamandé-Langle; Nadia Pellegrini Moïse (MDPI AG, 2022)
Considering the individual characteristics of positron emission tomography (PET) and optical imaging (OI) in terms of sensitivity, spatial resolution, and tissue penetration, the development of dual imaging agents for bimodal PET/OI imaging is a growing field. A current major breakthrough in this field is the design of monomolecular agent displaying both a radioisotope for PET and a fluorescent dye for OI. We took advantage of the multifunctionalities allowed by a clickable C-glycosyl scaffold to gather the different elements. We describe, for the first time, the synthesis of a cyanine-based dual PET/OI imaging probe based on a versatile synthetic strategy and its direct radiofluorination via [18F]F-C bond formation. The non-radioactive dual imaging probe coupled with two c(RGDfK) peptides was evaluated in vitro and in vivo in fluorescence imaging. The binding on αvβ3 integrin (IC50 = 16 nM) demonstrated the efficiency of the dimeric structure and PEG linkers in maintaining the affinity. In vivo fluorescence imaging of U-87 MG engrafted nude mice showed a high tumor uptake (40- and 100-fold increase for orthotopic and ectopic brain tumors, respectively, compared to healthy brain). In vitro and in vivo evaluations and resection of the ectopic tumor demonstrated the potential of the conjugate in glioblastoma cancer diagnosis and image-guided surgery.